The Influence of Competence and Work Environment on the Performance of State Civil Apparatus Through Motivation at The Regional Secretariat of Merangin District - Ahmad Khoiruddin Agung Saputro; M. Zahari; Fakhrul Rozi Yamali (Dinasti Publisher, 2024)
The purpose of this research is to obtain an overview and describe the competencies, work environment, motivation, and performance of Civil Servants, as well as to understand and analyze the direct and indirect effects of competencies and work environment on the motivation and performance of Civil Servants. The population in this study consists of 54 Civil Servants at the Regional Secretariat of Merangin Regency in the year 2024. The data analysis technique used in this research is path analysis, followed by hypothesis testing using the F-test (simultaneous) and t-test (partial). The path analysis results indicate that competencies and work environment have both direct and indirect effects on Civil Servants performance through work motivation. This explains that the better the competencies possessed by employees in performing their main tasks and functions, and the better the work environment perceived by Civil Servants, the more motivated the Civil Servants will be to improve their performance within the organization. This study concludes that competencies are in a high condition, the work environment is in a good condition, motivation is in a high condition, and Civil Servants performance is in a high condition.